Study of Outcome of Ischemic Stroke Patient With Atrial Fibrillation (TAJ: Journal of Teachers Association, 2018)
Atrial fibrillation (AF) is a common arrhythmia and a major risk factor for ischemic stroke, especially in the elderly. Patients with nonvalvular AF have a 5-fold excess risk of stroke. However, population-based data are scarce in patients who have experienced a first-ever ischemic stroke in the presence of AF regarding long-term risk of stroke recurrence and case-fatality rate. Aim of the study is to find out the outcome of ischemic stroke patients with Atrial Fibrillation. It was a descriptive type cross sectional study where 125 diagnosed cases of ischemic stroke were included. Presence of atrial fibrillation was detected by electrocardiogram. They were divided into two groups – those with atrial fibrillation and those without. Comparison was done between the two group in term of recurrence, mortality and clinical improvement. Atrial fibrillation was present in 22 (17.6%) of 125 patients with ischemic stroke. Those with AF were more frequently male, aged 45 years and older. The presence of AF was associated with high 3 months (Χ2 =4.562, df = 1, p